Effects of Vaccination with Altered Peptide Ligand on Chronic Pain in Experimental Autoimmune Encephalomyelitis, an Animal Model of Multiple Sclerosis - Tian, David H.; Perera, Chamini J.; Apostolopoulos, Vasso; Moalem-Taylor, Gila (Frontiers in Neurology, 2013)
Neuropathic pain is a chronic symptom of multiple sclerosis (MS) and affects nearly half of all MS sufferers. A key instigator of this pain is the pro-inflammatory response in MS. We investigated the behavioural effects of immunisation with a mutant peptide of myelin basic protein (MBP), termed altered peptide ligand (APL), known to initiate immune deviation from a pro-inflammatory state to an anti-inflammatory response in experimental autoimmune encephalomyelitis (EAE), an animal model of MS. Male and female Lewis rats were injected with vehicle control or with varying doses of 50 or 100 µg guinea pig MBP in combination with or without APL. APL-treated animals established significantly lower disease severity compared to encephalitogenic MBP-treated animals. Animals with EAE developed mechanical, but not thermal pain hypersensitivity. Mechanical pain sensitivities were either improved or normalised during periods of clinical disease in male and female APL-treated animals as compared to the encephalitogenic group. No significant changes to thermal latency were observed upon co-immunisation with APL. Together these data indicate that APL ameliorates disease states and selectively mediates an analgesic effect on EAE animals.